Response of heterogeneous ribonuclear proteins (hnRNP) to ionizing radiation and their involvement in DNA damage repair - Haley, Benjamin (2009)
PURPOSE: To determine the relationship between heterogeneous nuclear ribonucleoproteins (hnRNP) and DNA repair, particularly in response to ionizing radiation (IR). MATERIALS AND METHODS: The literature was examined for papers related to the topics of hnRNP, IR and DNA repair. RESULTS: HnRNP orchestrate the processing of mRNA to which they are bound in response to IR. HnRNP A18, B1, C1/C2 and K interact with important proteins from DNA Damage Response (DDR) pathways, binding DNA-dependent protein kinase (DNA-PK), the Ku antigen (Ku) and tumor suppressor protein 53 (p53) respectively. Notably, irregularities in the expression of hnRNP A18, B1, K, P2 and L have been linked to cancer and radiosensitivity. Sixteen different hnRNP proteins have been reported to show either mRNA transcript or protein quantity changes following IR. Various protein modifications of hnRNP in response to IR have also been noted: hnRNP A18, C1/C2 and K are phosphorylated; hnRNP C1/C2 is a target of apoptotic proteases; and hnRNP K degradation is controled by murine double minute ubiquitin ligase (MDM2). Evidence points to a role for hnRNP A1, A18, A2/B1, C1/C2, K and P2 in regulating double-stranded break (DSB) repair pathways by promoting either homologous recombination (HR) or non-homologous end rejoining (NHEJ) repair pathways following IR. CONCLUSIONS: HnRNP proteins play a pivotal role in coordinating repair pathways following exposure to IR, through protein-protein interactions and transcript regulation of key repair and stress response mRNA. In particular, several hnRNP proteins are critical in coordinating the choice of HR or NHEJ to repair DSB caused by IR.